Treatment of immunocompromised COVID‐19 patients with convalescent plasma - Fung, Monica (Transpl Infect Dis, 2020)
Immunosuppressed patients such as solid organ transplant and hematologic malignancy patients appear to be at increased risk for morbidity and mortality due to coronavirus disease 2019 (COVID‐19) caused by SARS coronavirus 2 (SARS‐CoV‐2). Convalescent plasma, a method of passive immunization that has been applied to prior viral pandemics, holds promise as a potential treatment for COVID‐19. Immunocompromised patients may experience more benefit from convalescent plasma given underlying deficits in B and T cell immunity as well as contraindications to antiviral and immunomodulatory therapy. We describe our institutional experience with four immunosuppressed patients (two kidney transplant recipients, one lung transplant recipient, and one chronic myelogenous leukemia patient) treated with COVID‐19 convalescent plasma through the Expanded Access Program (NCT 04338360). All patients clinically improved after administration (two fully recovered and two discharged to skilled nursing facilities) and none experienced a transfusion reaction. We also report the characteristics of convalescent plasma product from a local blood center including positive SARS‐CoV‐2 IgG and negative SARS‐CoV‐2 PCR in all samples tested. This preliminary evidence suggest that convalescent plasma may be safe among immunosuppressed patients with COVID‐19 and emphasizes the need for further data on the efficacy of convalescent plasma as either primary or adjunctive therapy for COVID‐19.